2018
DOI: 10.1108/jpmh-02-2018-0016
|View full text |Cite
|
Sign up to set email alerts
|

Stigma towards individuals who self harm: impact of gender and disclosure

Abstract: Purpose Non-suicidal self-injury (NSSI) is reasonably common, particularly among young people with prevalence rates of up to 25 per cent reported. Many factors contribute towards NSSI, including depression, anxiety and history of abuse and NSSI is a risk factor for suicide. Many people who engage in NSSI do not seek help, potentially due to concern about sigmatising attitudes. The purpose of this paper is to investigate the impact of gender and disclosure on stigmatising attitudes towards individuals who engag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 44 publications
4
47
0
Order By: Relevance
“…These results were consistent with previous evidence suggesting that NSSI is a stigmatized behavior (Burke et al, 2019;Law et al, 2009;Lloyd et al, 2018) and with studies demonstrating the presence of self-stigma among those with psychiatric disorders (Teachman et al, 2006). Teachman et al (2006) found that participants were more likely to endorse stigmatizing beliefs about psychiatric disorder as compared to physical illness regardless of the participants' health status.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These results were consistent with previous evidence suggesting that NSSI is a stigmatized behavior (Burke et al, 2019;Law et al, 2009;Lloyd et al, 2018) and with studies demonstrating the presence of self-stigma among those with psychiatric disorders (Teachman et al, 2006). Teachman et al (2006) found that participants were more likely to endorse stigmatizing beliefs about psychiatric disorder as compared to physical illness regardless of the participants' health status.…”
Section: Discussionsupporting
confidence: 92%
“…Previous empirical literature has demonstrated the presence of public stigma toward NSSI (Burke et al, 2019;Law et al, 2009;Lloyd et al, 2018), and this study provides evidence of self-stigma toward NSSI. Although previous research has suggested that individuals with psychiatric disorders do not demonstrate a positive in-group bias (Teachman et al, 2006), there is evidence demonstrating a reduced aversion to NSSI stimuli .…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Within lay communities, NSSI is often conceptualized primarily as a behavior that young women engage in by cutting their skin (Lewis, Mahdy, Michal, & Arbuthnott, 2014). Given the stigma associated with NSSI (Heath et al, 2011;Lloyd et al, 2018) and the stereotype of "who self-injures," men, older people, and people who engage in NSSI methods other than cutting may be more hesitant to label their behavior as NSSI on a single-item.…”
mentioning
confidence: 99%